Immune-mediated inflammatory diseases and risk of venous thromboembolism: A Mendelian randomization study - Lv, Xiaoshuo; Gao, Xixi; Liu, Jingwen; Deng, Yisen; Nie, Qiangqiang; Fan, Xueqiang; Ye, Zhidong; Liu, Peng; Wen, Jianyan (Frontiers in Immunology, 2022)
Background: Immune-mediated inflammatory diseases (IMIDs) have been associated with an increased risk of venous thromboembolism (VTE) in multiple observational studies. However, a direct causally relation between IMIDs and VTE remains unclear to date. Here, we used Mendelian randomization (MR) analysis to investigate causal associations between IMIDs and VTE. Materials and Methods: We collected genetic data from published genome-wide association studies (GWAS) for six common IMIDs, specifically inflammatory bowel disease (IBD), Crohn's disease (CD), ulcerative colitis (UC), rheumatoid arthritis (RA), psoriasis (PSO), and systemic lupus erythematosus (SLE); and summary-level data for VTE, pulmonary embolism (PE), and deep vein thrombosis (DVT) from the FinnGen database. Two-sample MR analysis using inverse variance weighting (IVW) was performed to identify causal associations between IMIDs and VTE/DVT/PE, and sensitivity analyses were implemented for robustness. Results: IVW analysis showed a causal relationship between genetically predicted UC (one type of IBD) and the risk of VTE (OR = 1.043, 95% CI: 1.013-1.073, p = 0.004) and DVT (OR = 1.088, 95% CI: 1.043-1.136, p  0.001), but we found no evidence of causality between UC and PE (OR = 1.029, 95% CI: 0.986-1.074, p = 0.19). In addition, no associations were observed between total IBD, CD, RA, SLE, or PSO and VTE/DVT/PE. Sensitivity analysis found no evidence for horizontal pleiotropy. Conclusion: This MR study provides new genetic evidence for the causal relationship between IMIDs and the risk of VTE. Our findings highlight the importance of active intervention and monitoring to mitigate VTE risk in patients with IBD, in particular those presenting with UC.